2013
DOI: 10.1108/02635571311289674
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating alternative industrial network organizations and information systems

Abstract: PurposeThe purpose of this paper is to present a simulation‐based evaluation method for the comparison of different organizational forms and software support levels in the field of supply chain management (SCM).Design/methodology/approachApart from widely known logistic performance indicators, the discrete event simulation model considers explicitly coordination cost as stemming from iterative administration procedures.FindingsThe method is applied to an exemplary supply chain configuration considering various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In earlier studies has been shown that in the majority of the cases the logistic cost can be reduced when changing from 'Logistic Segmentation' to 'Functional Consolidation' and even more if 'Network Integration' is applied (Mittermayer and Rodríguez 2008;Mittermayer and Rodríguez 2009). However, in highly uncertain environments additional coordination effort through iterative cycles is not compensated by an increase in coordination benefit (Mittermayer and Rodríguez 2013). Therefore in this exemplary simulation study further settings are studied regarding capacity load and forecast parameters.…”
Section: Simulation Model Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier studies has been shown that in the majority of the cases the logistic cost can be reduced when changing from 'Logistic Segmentation' to 'Functional Consolidation' and even more if 'Network Integration' is applied (Mittermayer and Rodríguez 2008;Mittermayer and Rodríguez 2009). However, in highly uncertain environments additional coordination effort through iterative cycles is not compensated by an increase in coordination benefit (Mittermayer and Rodríguez 2013). Therefore in this exemplary simulation study further settings are studied regarding capacity load and forecast parameters.…”
Section: Simulation Model Implementationmentioning
confidence: 99%
“…The simulation model has been developed by MITTERMAYER AND RODRÍGUEZ (2013). The notation is adapted from existing models (Pibernik and Sucky, 2007):…”
Section: Discrete Event Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation